COMPARISON OF HOGHORN ANALYSIS METHODS (Perner's Contacts, 2020)
The paper compares an aperture method and full-wave numerical simulations of hoghorn, which is used as a simple primary feed for reflector antennas or individually without reflector. The hoghorn consists of a sectoral horn flaring in only one plane and a parabolic cylinder. We briefly explain the calculations of hoghorn dimensions, aperture distributions and radiation patterns. This is suitable for numerical computations. We analyze the completely new simultaneous comparisons of the ample experiments with numerical results of both the aperture method and the numerical simulations. This enables to obtain innovative conclusions. Proposed improvements can diminish slight differences of one polarization between experiments and numerical simulations. We have used the described methods for the design of certain antennas for multilateration systems, such as Tamara and Vera passive radars, for civilian and military air traffic control, which greatly improve the accuracy of tracking aircrafts.
Keywords: air traffic control; antenna design; hoghorn; antenna radiation patterns; radar antennas; antenna measurements